Effect of Phototherapy on Transcutaneous vs Total Serum Bilirubin Level in Preterm Neonates- A Prospective Cohort Study - M Soumya; Vinod Chavan; Aishwarya Manthale; Kavitha S Konded4 (JCDR Research and Publications Pvt. Ltd., 2023)
Neonatal jaundice is one of the most common problems encountered in the first week after birth. Neonates who develop significant hyperbilirubinemia require phototherapy. Delay in the diagnosis and management of jaundice may lead to neonatal morbidity and mortality. Total Serum Bilirubin (TSB) estimation is considered the gold standard method. However, this invasive procedure causes pain, anxiety, and may lead to infection and iatrogenic anaemia, especially in preterm neonates. Transcutaneous Bilirubin (TcB) estimation, which measures bilirubin through the skin, has been proposed as an alternative screening method for hyperbilirubinemia in term and near-term neonates. Aim: To compare TcB to TSB in preterm neonates of 30-34 6/7 weeks gestational age before, during, and after phototherapy. Materials and Methods: This hospital-based prospective cohort study was conducted at SDMCMS&H, Dharwad, Karnataka, India, between December 2019 and November 2020. A total of 100 preterm neonates between 30 to 34 6/7 weeks of gestation with clinically suspected jaundice were enrolled in the study. TSB was measured in the laboratory using the Diazo Method, while TcB was measured using the Drager jaundice meter JM 103. TcB and TSB were measured and compared in preterm neonates with clinically suspected jaundice before phototherapy, during phototherapy (8 to 12 hours after initiation), and after 12-18 hours of discontinuation of phototherapy. The collected data was analysed statistically using the mean, standard deviation, dependent t-test, Karl Pearson's correlation coefficient, and scatter plots. Results: This study enrolled 100 neonates diagnosed with neonatal jaundice, of which 57 were males and 43 were females, resulting in a male-to-female ratio of 1:1.3. Phototherapy was administered to neonates with TSB values, with 79% of the babies between 30-32 weeks and 21% between 32-34 weeks. In the present study, TcB and TSB were compared before, during, and after phototherapy, and the results were analysed, showing statistical significance. The mean TcB levels were 12.05, 9.66, and 7.23 before, during, and after phototherapy, respectively. The mean TSB levels were 11.28, 10.16, and 7.65 before, during, and after phototherapy, respectively. Based on Karl Pearson's correlation coefficient, a positive correlation was found between TcB and TSB before (r=0.8319, p-value <0.001), during (r=0.6069, p<0.001), and after phototherapy (r=0.8154, p<0.001). Conclusion: TcB values are comparable to TSB values and can be adopted as the standard method to measure bilirubin levels in preterm babies in a clinical setting.